Area served by the South Pacific Commission - Australia. Division of National Mapping (Canberra : Natmap, 1980)
Lists participating governments and territories, with population at latest census.
"NMP 79/183.1".
Keywords: South Pacific Commission -- Maps; Oceania -- Maps